Bistable Organic Materials in Optoelectrical Switches: Two-Electrode Devices vs Organic Field Effect Transistors - Sworakowski, J.; Lutsyk, P. (Ukrainian Journal of Physics, 2022)
We present a short overview of research into properties of organic materials and structures that could be used in optoelectrical switches, i.e., switches in which changes in electrical properties are triggered by light of appropriate wavelengths. In particular, we describe the structures acting by virtue of reversible photochemical reactions occurring in photochromic molecular materials.